Novel Factor V C2-Domain Mutation (R2074H) in Two Families with Factor V Deficiency and Bleeding - Schrijver, I.; Houissa-Kastally, R.; Jones, C. D.; Garcia, K. C.; Zehnder, J. L. (Thrombosis and Haemostasis, 2002)
The molecular basis of Factor V deficiency has been defined in few patients only. We report a homozygous nucleotide change (G6395A) in two Tunisian probands with Factor V deficiency and bleeding episodes. This substitution results in the replacement of an arginine (R) by a histidine (H) in amino acid position 2074, located in the Factor V C2-domain. Mutations in this protein domain have not previously been described. Several lines of evidence support that this sequence variant is indeed disease causing: 1) Crystal structures of Factor V and molecular C2-domain modeling studies of H2074 suggest that the conserved R2074 is required for correct folding; 2) Structure-function studies of selective Factor V mutants (R2074A) demonstrate the importance of R2074 for structural stability of the Factor V C2-domain and for cofactor activity (1); 3) In Factor VIII, point mutations in codon 2209, which corresponds to position 2074 in Factor V, cause hemophilia A.
Keywords: Factor V deficiency; parahemophilia; inherited coagulation disorders; Factor V; bleeding